Funzione biopolitica delle frontiere nell’accoglienza a richiedenti asilo e rifugiati - Zorzetto, Sergio (Cambio. Rivista sulle Trasformazioni Sociali, 2017)
Based on the Deleuze and Guattari’s elaboration of the ethnological concept of segmentarity, the article advances an interpretation of the ongoing reorganisation of (Italian) frontiers in response to the international migratory fluxes. From this point of view, the tree and the circle join the line as geometrical metaphors able to give back the structure and the functions of the frontiers and their capacity to articulate state powers (sovereign, disciplinary and biopolitical). The reorganisation of frontiers outlines the construction of a liminal space and time within the national borders in which these state powers are enforced upon migrant populations. It is a sort of internalisation of frontiers that couples with their already highlighted externalisation. Adopting a panoramic glance, the coupled processes of internalisation and externalisation of frontiers draw a transnational and interstate territory. Along this border territory, however discontinuous and stray, migrants flow and through it the contemporary figures of asylum seekers and refugees are constructed.